A Descriptive analysis of the Finnish treasury bond market 1991-1999 - Matti Keloharju; Markku Malkamäki; Kjell G. Nyborg; Kristian Rydqvist (Bank of Finland, 2002)
This paper presents a descriptive analysis of the primary and secondary market for Finnish treasury bonds.The paper focuses on three issues.First, we report basic descriptive statistics such as auction volumes and secondary market yields and volumes.Second, we estimate the revenues earned by primary dealers from the treasury bond market.Third, we analyse the development of the price of the auctioned bonds, relative to other benchmark bonds, around the time of the auction.We find evidence of a price decrease in the auctioned bond series before the auction and a price increase after the auction.This pattern is strongest for 1992-1994 when Treasury funding needs were heavy and secondary market trading volume of treasury bonds was modest.
URN:NBN:fi:bof-20140807221
Keywords: D44; G12; G20; 330; treasury bond auctions; secondary market